2013
DOI: 10.1140/epjc/s10052-013-2618-0
|View full text |Cite
|
Sign up to set email alerts
|

Ion-beam excitation of liquid argon

Abstract: The scintillation light of liquid argon has been recorded wavelength and time resolved with very good statistics in a wavelength interval ranging from 118 nm through 970 nm. Three different ion beams, protons, sulfur ions and gold ions, were used to excite liquid argon. Only minor differences were observed in the wavelengthspectra obtained with the different incident particles. Light emission in the wavelength range of the third excimer continuum was found to be strongly suppressed in the liquid phase. In time… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 58 publications
2
44
0
Order By: Relevance
“…This work corroborates the model from [19], which attributes the intermediate component to a feature intrinsic to LAr, and confirms the existing evidence for delayed TPB emission. Both are measured for the first time here in a large LAr-based particle detector.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…This work corroborates the model from [19], which attributes the intermediate component to a feature intrinsic to LAr, and confirms the existing evidence for delayed TPB emission. Both are measured for the first time here in a large LAr-based particle detector.…”
Section: Introductionsupporting
confidence: 90%
“…Some authors attributed this component to late emission of the wavelength shifter 1,1,4,4tetraphenyl-1,3-butadiene (TPB) [20], making it an instrumental effect. However, the intermediate component was also observed in [19], where the pulseshape was measured without the use of a wavelengh-shifter. This supports the hypothesis that the intermediate component is a feature intrinsic to LAr scintillation physics.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In summary, it has been found that the efficient energy transfer from argon to xenon which is well known from the gas phase is also present in the liquid phase. This had already been observed in the context of recording emission spectra from nominally pure liquid argon [13,18,23] and Fig. 7.…”
Section: Discussionsupporting
confidence: 61%
“…The emission was found in the context of a series of experiments on the emission and absorption features of liquid noble gases [1,3,4,5]. This study was motivated by the fact that liquid rare gases are presently often used in large quantities as the detector material in rare event physics, e.g., the search for the neutrinoless double-beta decay (GERDA Phase II uses a liquid argon veto [6], EXO uses liquid xenon [7]) and the direct dark matter search (Liquid argon: WArP [8], ArDM [9,10], DarkSide [11]; Liq-arXiv:1511.07722v1 [physics.ins-det] 24 Nov 2015 uid xenon: XENON100 [12], LUX [13]).…”
Section: Motivationmentioning
confidence: 99%